The Polycistronic miR166k-166h Positively Regulates Rice Immunity via Post-transcriptional Control of EIN2 - Salvador-Guirao, Raquel; Hsing, Yue-ie; San Segundo, Blanca (Frontiers in Plant Science, 2018)
MicroRNAs (miRNAs) are small RNAs acting as regulators of gene expression at the post-transcriptional level. In plants, most miRNAs are generated from independent transcriptional units, and only a few polycistronic miRNAs have been described. miR166 is a conserved miRNA in plants targeting the HD-ZIP III transcription factor genes. Here, we show that a polycistronic miRNA comprising two miR166 family members, miR166k and miR166h, functions as a positive regulator of rice immunity. Rice plants with activated MIR166k-166h expression showed enhanced resistance to infection by the fungal pathogens Magnaporthe oryzae and Fusarium fujikuroi, the causal agents of the rice blast and bakanae disease, respectively. Disease resistance in rice plants with activated MIR166k-166h expression was associated with a stronger expression of defense responses during pathogen infection. Stronger induction of MIR166k-166h expression occurred in resistant but not susceptible rice cultivars. Notably, the ethylene-insensitive 2 (EIN2) gene was identified as a novel target gene for miR166k. The regulatory role of the miR166h-166k polycistron on the newly identified target gene results from the activity of the miR166k-5p specie generated from the miR166k-166h precursor. Collectively, our findings support a role for miR166k-5p in rice immunity by controlling EIN2 expression. Because rice blast is one of the most destructive diseases of cultivated rice worldwide, unraveling miR166k-166h-mediated mechanisms underlying blast resistance could ultimately help in designing appropriate strategies for rice protection.